John Henryism, psychological labor, and control-value theory: Race, ethnicity, and situational coping for student success - Torsney, Benjamin M.; Burke, Kathryn M.; Torsney, Cheryl B.; Lombardi, Doug (Frontiers in Education, 2022)
This study explored the integration of John Henryism—defined as effortful, active coping in response to environmental stress—into control-value theory. Specifically, we were interested in how this process differed among identity groups. We used measures of John Henryism (JHAC-12; James et al., 1987), control-value theory, and momentary engagement (Record of Experience; Shernoff et al., 2016) on a school-based task. Results demonstrated the following: identifying as a first-generation college student predicted John Henryism; value significantly predicted cognitive engagement and positive emotion; and control lowered negative emotions. Identifying as a first-generation college student corresponded to higher levels of John Henryism and control. Identifying as female led to a decrease in positive emotions, but an increase in value. Similarly, identifying as Black was associated with a decrease in control, but also a decrease in negative emotions. Indirect effects showed that identifying as a first-generation college student led to an increase in John Henryism followed by (1) an increase in value, (2) an increase in perceived control, or (3) an increase in value with attendant positive emotions. Findings indicate that John Henryism integrates into control-value theory and contributes to momentary engagement on a school-based task.